The range and nature of reproductive health research in the occupied Palestinian territory: a scoping review - Aisha Shalash; Hasan M Alsalman; Alaa Hamed; Mai Abu Helo; Rula Ghandour; Loai Albarqouni; Niveen ME Abu Rmeileh (BMC, 2019)
Abstract Background In order to set research priorities for reproductive health in the occupied Palestinian territory, it is vital to know what current research has been done in the field of reproductive health. The purpose of this scoping review is to examine the range and nature of reproductive health research in the occupied Palestinian territory and to identify research gaps in the existing literature. Methods We searched four databases: EMBASE, PubMed, CINAHL, and Popline. We included studies that: (i) are published (with an abstract); (ii) relevant to reproductive health; (iii) Palestinians living in Palestine; (iv) participants over the age of 15 years; and (v) restricted to human research. Three independent reviewers screened title and abstracts, and extracted data from included articles. We conducted quantitative and qualitative analyses. Results Of 1025 titles and abstracts screened, 145 articles were included. 52 (36%) articles were conducted in community setting and 34 (24%) were conducted in hospitals. There were 5 (3%) experimental studies. 15 articles had more than one main theme; 160 subthemes overall were identified. The most frequently studied theme was labor and delivery (n = 19; 12%). One article discussed adolescent reproductive health and menopause while no articles discussed men's reproductive health. Conclusions 91% of the research conducted is observational. The focus of reproductive health research was to understand the topic, community and providers' perceptions and knowledge. Articles related to the quality of services were limited. It is also important to research the reproductive health of women outside of reproductive age, men, and adolescents.